Fake News: um estudo dos mecanismos discursivos de notícias falsas relacionadas à pandemia de Covid-19. - Davidson Henrique da Silva Padrão (2024)
This dissertation examines fake news in the digital age, focusing on narratives related to Covid-19 vaccination in Brazil. The goal is to understand, both theoretically and practically, this phenomenon through the lenses of Bakhtin, of Marcuschi and French Semiotics. We discuss whether fake news constitutes (or not) a new discursive genre and highlights the intersection between the Attention Economy and the dissemination of misinformation, especially during the Covid-19 pandemic. The research connects these dynamics to the Brazilian context, highlighting the role of the Fake News Inquiry and underscoring ethical challenges. In order to critically analyze the selected fake news, we used French Semiotics, through the generative path of meaning, so as to reveal the discursive strategies employed in the production of these misleading narratives. Methodologically, it is a qualitative research that delimited the corpus from official sources and specific periods, providing a critical analysis of the discursive strategies used. The results highlight not only the manipulation of discourse but also its insertion into broader social dynamics. The dissertation seeks to contribute to the theoretical and practical understanding of this phenomenon, alerting to the threat to democracy and accurate information in the digital age. The research reinforced the urgency of adaptive strategies to protect democratic integrity and truth, emphasizing the importance of interdisciplinarity in fake news analysis. The complexity of this phenomenon requires regulatory approaches, civil society actions, and digital platform responsibility to effectively address the challenges of the distorted information era.